Sistem Informasi Pendaftaran Siswa Baru Berbasis Web Pada SMK Ma’arif NU 1 Kemranjen - Fanny Fatma Wati; Elfiatun Nurul Hidayah; Rousyati Rousyati; I’dha Rhamdani Arif (Universitas Bina Sarana Informatika, 2019)
Abstract: The registration of students is only carried out in several stages, such as inputting the student's personal data, completeness of the requirements file, and announcement of selection results. However, because the new student registration system in Ma'arif NU 1 SMK Kemranjen is still manual, the new student registration service is still considered ineffective and time efficient, because prospective new students must wait for long service, besides the risk of prospective new student documents tucked into other documents because too many docu ments from prospective students are quite large. So we need a new student registration information system at Ma'arif NU 1 Kemranjen Vocational High School to provide better service. Research using methods of observation, interviews and literature studies. The used method in the development of this system is SDLC (Life Cyce Development System) with the waterfall process model. With this system, it is expected that it can support registration data processing so that it is more structured, efficient and effect ive. As well as for community service that is as an information center for schools in disseminating information so that the general public can quickly find accurate information. Keywords: Information Systems, Registration, Web based.